Identification of Magelang Ducks to Analyze Morphological Diversity in Ngadirojo Village, Secang District, Magelang Regency - Ayu Rahayu; Budi Santoso; Nadia Ade Luthfiana (Universitas Tidar, 2019)
Magelang duck is one of the productive local poultry producing meat and eggs. This study aims to compare the production and quality of eggs between local ducks at duck breeding centers in Ngadirojo Village, Secang District, Magelang Regency. The material used was 11 samples of ducks and eggs from different breeders. Based on the results of the study it was found that the average morphological measurements in ducks are bodyweight of 1.94 kg, body length 30.67 cm, neck length 14.18 cm, chest circumference 39.09 cm, and body temperature 40.18 cm. The average quality of Magelang duck eggs is egg weight of 64.46 gr, egg index 1.24 cm, eggshell thickness 0.06 cm, egg length 5.63 cm, and egg diameter 4.54 cm. The average albumen weight was 26.47 gr, yolk weight 23.69 gr, albumen width 8.87 cm, yolk width 4.49 cm, albumen height 0.77 cm, and yolk height 2.00 cm. The morphology of duck size will greatly affect egg production. The weight of female and male ducks is almost the same, ranging from 1.5-2 kg. Magelang duck egg production is about one grain every day. Each egg production will be different. This can be influenced by several factors including the quality of the seeds and the feed system that is given. Standard normal egg weight ranges from 65-70 grams. In maintenance, every 10 female ducks will be added by 1 male duck.Keywords: Identification, Morphology, Magelang Duck, Ngadiroj